Embodying Learners’ Semasiological Disparateness in an English First Additional Language Classroom - Kufakunesu Zano (Universitas Pendidikan Mandalika, 2024)
Language-in-education policy in the apartheid era in South Africa reflected a divide-and-rule strategy, which stipulated that each ethnic group was to be taught in its language. Thus, the post-1994 period in South Africa involved a dramatic re-imagination of the country from a racially divided nation to a diverse but united, non-racial nation. This is pertinent to South Africa, a linguistically diverse country whose history of language in education has been shaped by political interests, as well as pedagogical considerations. Against this background, since the impact of cultural diversity on education policy and reforms is a strategically significant issue for us all, this study sought to explore how Grade 4 English First Additional Language (EFAL) teachers incorporate Grade 4 EFAL learners’ linguistic diversity in teaching and learning. For this qualitative study, 10 Grade 4 teachers in 5 primary schools in one district in South Africa were used as respondents. The researcher used one-on-one telephonic interviews to collect data. The results revealed that teachers acknowledge the need to use some approaches to support oral language development. Besides, teachers use a range of strategies, from translanguaging, and code-switching to translation, to encourage learners to use their home languages to develop proficiency in the EFAL. Also, the study has shown that cooperative language learning, which shares some characteristics with communicative language teaching helps learners develop a great liking of EFAL.